2021
DOI: 10.1002/smj.3308
|View full text |Cite
|
Sign up to set email alerts
|

Board design and governance failures at peer firms

Abstract: Research Summary Our study introduces board committees as a crucial determinant of board actions. We examine how directors who structurally link different board committees—referred to as multi‐committee directors (MCDs)—explain why some board actions are merely symbolic while others are more substantive. As a baseline, we argue that boards in general respond to financial restatements at peer firms by symbolically appointing new directors who are relatively inexperienced and unlikely to have a substantive impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…The presence of an independent director or board and independence in the nomination and remuneration committee are measured using a dummy variable, giving a value of 1 if there are independent members and a score of 0 if not (Appiah and Chizema, 2016;Kanapathippillai et al, 2016;Ruigrok et al, 2006), which used the percentage of the number of independent members (Eulaiwi et al, 2016;Nyambia and Hamdan, 2018). The number (size) of nomination and remuneration committee members and meetings is measured by adding all committee members and the number of meetings in one year (Alkalbani et al, 2019;Appiah and Chizema, 2016;Gai et al, 2021). For experience, monitoring and expertise, Chaudhry et al (2020) used a dummy variable given a score of 1 if the committee chairperson had expertise in human resources.…”
Section: Measurement and Results Review Of Research 51 Different Meas...mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of an independent director or board and independence in the nomination and remuneration committee are measured using a dummy variable, giving a value of 1 if there are independent members and a score of 0 if not (Appiah and Chizema, 2016;Kanapathippillai et al, 2016;Ruigrok et al, 2006), which used the percentage of the number of independent members (Eulaiwi et al, 2016;Nyambia and Hamdan, 2018). The number (size) of nomination and remuneration committee members and meetings is measured by adding all committee members and the number of meetings in one year (Alkalbani et al, 2019;Appiah and Chizema, 2016;Gai et al, 2021). For experience, monitoring and expertise, Chaudhry et al (2020) used a dummy variable given a score of 1 if the committee chairperson had expertise in human resources.…”
Section: Measurement and Results Review Of Research 51 Different Meas...mentioning
confidence: 99%
“…found that the size of the nominating committee increases the gender diversity of the board. Gai et al (2021) find the number of committees increases with new directors, new directors with board experience and new directors with audit experience. Therefore, we believe that the greater the number of committee members, the greater the supervision of the board's performance and the higher the quality of the board candidates who will lead the company.…”
Section: Number Of Members and Frequency Of Meetings Nomination And R...mentioning
confidence: 99%
See 1 more Smart Citation
“…We build on this approach and apply it to boards of directors to construct a dynamic intrafirm board knowledge network, wherein knowledge exchanges occur when two directors with knowledge stocks in two distinct functional domains are linked through joint committee memberships on the board (i.e., two directors who have distinct, yet complementary knowledge stocks and share proximity through joint committee memberships are more likely to have a functional relationship and exchange knowledge with one another) 2 . Research has provided evidence that key board processes (e.g., decision‐making) largely take place in board committees (Brandes et al, 2016; Gai et al, 2021; Kolev et al, 2019) and that directors typically serve on multiple board committees simultaneously (Brandes et al, 2016), providing opportunities for knowledge exchange.…”
Section: Constructing Board Intrafirm Knowledge Networkmentioning
confidence: 99%
“…FinTech provides ease of transaction in the financial field and aims to maximize the use of technology in speeding up financial services (Purba, 2020). FinTech is more dynamic in adapting to changes in the financial services sector (Chiu & Iris, 2016); (Gai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%